(untitled) (Journal of Parents and Teachers, 2025)
What happens when heritage, intercultural exchange, and active learning come together in the heart of Europe? Four students from Comillas experienced it firsthand in Bosnia and Herzegovina, as part of an international project that allowed them to excavate the past, learn alongside peers from across Europe, and rethink teaching from a global, interdisciplinary, and deeply human perspective.